Melatonin supplementation reduces delirium incidence in critically ill patients: a systematic review and meta-analysis - Wu, Xiaoyu; Hu, Panxin; Wu, Haopeng; Zhang, Kai; Ying, Jianzhi (Frontiers in Pharmacology, 2026)
BackgroundDelirium represents a common and severe neuropsychiatric complication among critically ill individuals, often leading to extended hospital stays, elevated mortality risk, and persistent cognitive decline. Disruption of circadian sleep-wake rhythms is a major pathogenic factor, implying that melatonin may hold therapeutic potential in this context. Nonetheless, evidence regarding the effectiveness of melatonin in preventing delirium among patients in intensive care unit (ICU) remains inconsistent.ObjectiveThis meta-analysis aimed to systematically evaluate the effects of melatonin and melatonin receptor agonists on the incidence and duration of delirium, length of ICU stay, and mortality among adult critically ill patients.MethodsWe conducted a systematic review and meta-analysis of randomized controlled trials (RCTs). A comprehensive search was performed in PubMed, Embase, Scopus, and Cochrane CENTRAL from inception until 10 October 2025. Only RCTs comparing melatonin or ramelteon with placebo or standard care in adult ICU patients were included. The primary outcome was the incidence of delirium. Secondary outcomes included duration of delirium, length of ICU stay, and overall mortality.ResultsA total of 22 RCTs involving 3706 patients were included. Pooled analysis demonstrated that melatonin administration was associated with a significant reduction in the incidence of delirium compared to the control group (Risk Ratio [RR] 0.75, 95% Confidence Interval [CI] 0.63 to 0.90, P = 0.001, I2 = 50%). However, melatonin did not significantly affect the duration of delirium (Mean Difference [MD] 0.18 days, 95% CI -0.16 to 0.52, P = 0.56, I2 = 45%), length of ICU stay (MD -0.45 days, 95% CI -1.10 to 0.20, P = 0.09, I2 = 68%), or overall mortality (RR 0.92, 95% CI 0.79 to 1.06, P = 0.25, I2 = 0%).ConclusionAmong critically ill adults, melatonin supplementation is effective in reducing the incidence of delirium. However, it does not appear to shorten the duration of delirium, reduce ICU stay, or improve survival. These findings support the use of melatonin for delirium prevention but suggest its benefits may be limited to reducing occurrence rather than altering the course of established delirium or other clinical outcomes.Systematic Review Registrationhttps://osf.io/95je7.